The birth certificate : an American history - Pearson, Susan J. (The University of North Carolina Press, 2021)
"For many Americans, the birth certificate is a mundane piece of paper, unearthed from deep storage when applying for a driver's license, verifying information for new employers, or claiming state and federal benefits. Yet as Donald Trump and his fellow 'birthers' reminded us when they claimed that Barack Obama wasn't an American citizen, it plays a central role in determining identity and citizenship. Here, award-winning historian Susan J. Pearson traces the document's two-hundred-year history to explain when, how, and why birth certificates came to matter so much in the United States"--